Depression, post-traumatic stress disorder, suicidality and self-harm among people who inject drugs: A systematic review and meta-analysis. (1st February 2020) - Colledge, Samantha; Larney, Sarah; Peacock, Amy; Leung, Janni; Hickman, Matt; Grebely, Jason; Farrell, Michael; Degenhardt, Louisa
Highlights: Nearly 1 in 3 people who inject drugs meet a clinical diagnosis of depression. Around one in four people who inject drugs has ever attempted suicide. Self-harm and PTSD appear to be common among people who inject drugs. Abstract: Background: A range of negative experiences and circumstances that are common among people who inject drugs (PWID) are risk factors for developing mental disorders. Despite this, there has been no systematic review of the prevalence of mental health indicators among PWID. Thus, we aimed to estimate the prevalence of depression, post-traumatic stress disorder (PTSD), suicidality and self-harm among PWID. Methods: We searched the peer-reviewed and grey literature for data on depression, PTSD, suicidality and non-suicidal self-harm among PWID from sources published from 2008-2018. We pooled estimates of depression and suicidality using random-effects meta-analysis and provided a narrative summary of estimates of PTSD and self-harm. Findings: We found 23 studies that reported on these mental health indicators among PWID. The pooled estimate for current severe depressive symptomology was 42.0 % (95 % confidence interval [CI] = 21.3, 62.8 %), and for a depression diagnosis was 28.7 % (95 % CI = 20.8, 36.6 %). With much variation, the pooled lifetime prevalence of a suicide attempt was 22.1 % (95 % CI = 19.3, 24.9 %). There were only two studies each that reported on PTSD and non-suicidal self-harm among PWID. Interpretation: Recent data investigating these mental health indicators among PWID was limited, particularly from low- and middle-income countries. Even so, estimates were high and call for further research into the epidemiology of such mental health disorders and self-harming behaviours, as well as the promotion of integrated mental health and substance dependence treatment. Finally, incorporating suicide prevention strategies into services accessed by PWID must be considered as a harm reduction priority.